Pengaruh Struktur Kepemilikan dan Kebijakan Dividen terhadap Tunneling : concentration ownership, dividend policy, ownership structure, managerial, tunneling - Rahmawati, Wahidah; Rohman, Abdul (Owner : Riset dan Jurnal Akuntansi, 2024)
Concentrated ownership structure of a company leads to the ability majority shareholders to control the company which can be used to take opportunistic actions. This study to examine the effect of ownership strucuture proxied by managerial ownership, institusional ownership, foreign ownership, public ownership and another variables, dividend policy as well as listed on the Indonesia Stock Exchange in 2020-2022. Tunneling is the transfer of resources out of the company for the interests of controlling shareholders. this type of research is classified as quantitative and uses secondary data from www.idx.co.id. The number of samples is generated by purposive sampling. Sampling of 36 companies according to the criteris multiplied by 3 years of company period making. Logistic regression is the hypothesis test used in this study. The result of this study indicate that managerial ownership has a positive effect on tunneling, while institusional ownership, foreign ownership, public ownership, and dividend policy don not affcet tunneling.